Strategi Mengajar Guru Pesantren dalam Meningkatkan Kedisiplinan Santri di Pondok Pesantren Al-Fathimiyah Telukjambe Timur - Tiara Ekha Lusviyanti; Oyoh Bariah; Sayan Suryana (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Islamic boarding school is an Islamic educational institution that grows and is recognized by the surrounding community, with a dormitory system (complex) where students receive religious education through a recitation system or madrasa which is fully under the guidance of a central figure, namely the cleric with a mosque as the central point that animates it. . Viewed from the point of view of science taught in Islamic boarding schools are divided into two forms, namely; salafi pesantren (traditional/classical) khalafist pesantren (modern). Al-Fathimiyah Islamic Boarding School is a boarding school that adheres to a modern traditional education system where the students study classical books and also study general subjects in general. In improving the discipline of students, pesantren teachers have their own strategies that are applied to improve student discipline. However, the researchers found a lack of understanding of the students towards the level of discipline and caused some students to underestimate or ignore the rules and regulations of Islamic boarding schools, thus making students who did not violate the footsteps of their friends. It is this bad influence that makes teachers and boarding school administrators not stay silent and strive continuously in enforcing student discipline. The researcher used this type of research with descriptive qualitative methods. Collecting data using observation and interview techniques and starting from several supporting theories in the field that are used as conditions for scientific objects ranging from strategic management applied by Islamic boarding schools to taking advantage of situations and conditions that occur in the field related to student discipline at school. . The results showed that the strategies that are often used by Islamic boarding school teachers in improving the discipline of students include: habituating students to always behave disciplined in every boarding activity in accordance with the rules of the Islamic boarding school, giving advice and punishment if there are students who violate and do not obey the rules. boarding school, providing motivation and direction by the pesantren teacher to each of his students